Modern multiple myeloma therapy: deep, sustained treatment response and good clinical outcomes. (16th February 2017) - Landgren, O.; Iskander, K.
Abstract: In the USA at the beginning of this century, the average overall survival in patients with multiple myeloma was about 3 years. Around that time, three drugs (bortezomib, lenalidomide and thalidomide) were introduced for the treatment of multiple myeloma and, in 2012, carfilzomib received accelerated approval by the US Food and Drug Administration (FDA). Driven by access to better drugs, median overall survival in younger patients (aged <50 years) was >10 years by 2014. The FDA approved 14 new drugs for the treatment of cancer in 2015; four of these were approved for the treatment of myeloma (panobinostat, daratumumab, elotuzumab and ixazomib). In 2015 and 2016, expanded label indications were approved by the FDA for lenalidomide and carfilzomib, respectively. The recent increase in approved, highly effective combination therapies for patients with multiple myeloma has led the way to redefining the goals of therapy. Here, we review and provide a clinical perspective on the treatment goals and management of multiple myeloma in the era of modern therapy. Recent meta‐analyses show that minimal residual disease (MRD) negativity is associated with longer progression‐free and overall survival in patients with multiple myeloma. With the use of modern combination therapy, large proportions (>60–70%) of newly diagnosed multiple myeloma patients achieve complete responses and MRD negativity. Modern combination therapies induce rapid, deep and sustainable responses (including MRD negativity), supporting a treatment paradigm shift away from palliative two‐drug combinations towards the use of modern, potent, three‐ or four‐drug combination regimens in early lines of therapy. Data support the use of modern therapy upfront rather than reserving it for later stages of the disease. As survival time increases with modern combination therapies, development of early reliable surrogate end‐points for survival, such as MRD negativity, are needed for expedited read‐out of future randomized clinical trials.